From Simulation to Practice: Factors Influencing Training Transfer Among Nurse Anaesthetists – A Qualitative Study - Xiaoling Yu; Liangmeng Yu; Qianxi Zhu (Journal of Clinical Nursing, 2026)
ABSTRACT Aim To explore factors influencing the transfer of simulation‐based training to clinical practice among nurse anaesthetists. Design An exploratory descriptive qualitative study guided by Transfer of Training Theory. Methods Semi‐structured, in‐depth interviews were conducted with 23 nurse anaesthetists from tertiary hospitals across five Chinese provinces between October 2025 and January 2026. Participants were recruited using purposive and snowball sampling. The interview guide was informed by Transfer of Training Theory, relevant literature and team deliberation. Data were analysed using primarily deductive content analysis while allowing inductive categories to emerge. Results Three themes were identified: individual readiness for transfer, training design characteristics, and workplace contextual conditions. Transfer was facilitated by patient‐safety motivation, self‐efficacy, and reflective adaptability and constrained by limited contextual realism, insufficiently individualised debriefing, weak follow‐up evaluation, and limited organisational support. Conclusion Transfer from simulation to clinical practice is shaped by interacting individual, training and workplace factors. Clinically aligned scenarios, individualised debriefing, follow‐up evaluation and organisational support may strengthen clinical application in anaesthesia nursing. Implications for the Profession and/or Patient Care Simulation‐based training should be organised as a pathway to clinical application rather than as an isolated educational event. At the unit level, scenarios should reflect actual anaesthesia nursing workflows and structured, individualised debriefing may involve appropriately prepared senior physicians and experienced nurse anaesthetists. Nursing managers can hold regular post‐training meetings, assess clinical application at 3–6 months and incorporate key practices into departmental protocols or standard operating procedures. Impact This study identifies actionable multilevel factors that can inform simulation design and post‐training support for nurse anaesthetists. Reporting Method The study adhered to the COREQ checklist. Patient or Public Contribution No patient or public contribution.